Affective Sciences through the Chemical Senses - Valentina Parma (Frontiers Research Topics, 2017)
In people's minds, smells, flavors and affective phenomena are perceived as closely linked. But is it genuinely the case? The scientific study of this question is a rapidly expanding field, both in healthy and in clinical populations. Although still under-studied in comparison to other sensory modalities, chemical senses have proven to bring unique knowledge in the understanding of affective phenomena. In this context, this Research Topic is aimed to offer a snapshot of the present knowledge and questions raised in this field. Topics include, but are not limited to: affects elicited by odors and/or flavors in different individuals, contexts or cultures; emotional potency of odors in guiding human behavior and cognition (e.g. attention, memory formation, decisions and choices, withdrawal and approach behavior); affects communicated by body odors; affect regulation disorders and chemosensory perception. Studies on the biological underpinnings of these effects are also included.